Thermal characteristics in round tube fitted with serrated twisted tape - Eiamsa-Ard, Smith; Promvonge, Pongjet (My University, 2010)
The article presents an investigation of the effect of twisted tape with serrated-edge insert on heat transfer and pressure loss behaviors in a constant heat-fluxed tube. In the experiments, the serrated twisted tape (STT) was inserted into the entire test tube with a constant twist ratio in order to generate a continuous swirling airflow. Two geometry parameters of the STT to be considered in the present work are the serration width ratio and the serration depth ratio. The measurements have been conducted for the airflow rate based on Reynolds numbers in the turbulent regime from 4000 to 20,000. The experimental results of the STT inserted tube are compared with those of the plain tube fitted with typical twisted tape (TT). The results show that the heat transfer rate in terms of Nusselt number, Nu increases with the rise in the depth ratio but decreases with raising the width ratio. The heat transfer rate is up to 72.2% and 27% relative to the plain tube and the TT inserted tube, respectively. The use of the STT leads to higher heat transfer rate and friction factor than that of the TT for all cases. The thermal performance factor of the STT tube under constant pumping power is evaluated and found to be above unity indicating that using the STT tube is advantageous over the TT tube or the plain tube. In addition, the empirical correlations developed by relating the serration width ratio, serration depth ratio and Reynolds number are determined. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Friction factor; Heat transfer; Serrated twisted tape; Swirl flow; Typical twisted tape